(3QSGdI aj JMbjb GdfHhIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCdJ GUdMc Gddg JYGdi Gf GLYdg Led eG NWH ai ERGdi GdTchc GdeJCcOI YfOc ai JUOjb GdfHhI s
(3BNQgG (B:s
(3hGdeSJYed ai GddZGJ Cf GdTF GdeDOi Edi TF jSei HGHkG aGdSHYI GdeDOjI Edi GdfGQ SejJ CHhGHkG dgG hGdKeGfjI GdeDOjI Edi GdLfI SejJ CHhGHkG dgG agPg EHGfI LejY GdeSGFd Ydi GdEjLGR hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds